(untitled) (Tidsskrift for Praktisk Teologi, 2020)
This article presents historical and contemporary perspectives on institutional chaplaincy with a special focus here on hospital chaplaincy in Sweden. The term spiritual care is used as the overall descriptor of all the different functions and activities in which the hospital chaplain is engaged. In this overview article we hope the reader will get a glimpse into the complex ways in which hospital chaplaincy has evolved and the numerous societal actors and political decisions that have been and continue to be involved in how the work of the hospital chaplain is both defined as well as organised in terms of the larger societal structure. In our contemporary perspective, it is important to understand the different kinds of challenges as well as possibilities that multi-cultural and multi-faith needs have raised in the Swedish cultural context, considered to be one of the most secular in the world. These challenges and possibilities have brought to the forefront critically important insights related to the understanding of spiritual care as a dimension of healthcare that is important for all persons, for all patients, and that person-centred care necessitates the inclusion of this dimension.